Pertanggungjawaban Pidana bagi Notaris yang Melakukan Pemalsuan Akta Perjanjian Pengikatan Jual Beli dan Kuasa Menjual (Studi Kasus Putusan Mahkamah Agung Nomor 933 K/Pid/2023) - Muhammad Fayyadh Lubis; Alvi Syahrin; suprayitno (CV Rewang Rencang, 2025)
Notaries who commit forgery of Sale and Purchase Binding Agreement deeds and Power of Attorney to Sell can be held criminally liable based on Supreme Court Decision Number 933 K/Pid/2023. The notary was sentenced to criminal sanctions in accordance with Article 264 paragraph (1) in conjunction with Article 88 of the Criminal Code with a punishment of 5 years imprisonment, administrative sanctions in the form of revocation of practice license by INI and the Ministry of Law, as well as civil sanctions in the form of compensation to the injured party. Deed forgery constitutes a violation of the Notary Position Law and the Criminal Code which has fatal consequences for legal certainty and public trust in the notary profession.